Peningkatan Hasil Belajar Pendidikan Agama Islam Dengan Menggunakan Model Problem Based Learning UPTD SDN 02 Tanjuang Bungo - Dila Yanti Safitri; Syawaluddin Syawaluddin; Deslita Deslita; Hidayati Hidayati; Yeni Susila; Delfiyanti Delfiyanti (Jurnal Pendidikan Tuntas, 2024)
Education aims to improve the quality and quantity of students. The selection of the right learning model in the learning process greatly affects the high and low learning outcomes of students. The learning model is an approach that can be taken by educators so that the teaching and learning process runs effectively so that educational goals are achieved. The problem in this study is the low learning outcomes of students in Islamic Religious Education subjects because the learning model used is still not varied and conventional. To overcome these problems, researchers applied the Problem Based Learning (PBL) Model with the aim of improving Islamic Education learning outcomes in class V UPTD SDN 02 Tanjuang Bungo students. This research uses the type of classroom action research (PTK). The subjects in this study were class V UPTD SDN 02 Tanjuang Bungo students totaling 11 students consisting of 4 male students and 6 female students. Classroom action research was carried out in four cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it shows that the average learning outcomes of students have increased. It is known that the KKTP value that has been determined from the school is 70. In pre-research, it is known that 4 students have reached KKTP with a percentage of 36% and 7 students have not reached KKTP with a percentage of 64%. In cycle I, it has increased as many as 6 students have reached KKTP with a percentage of 55% and 5 students have not reached KKTP with a percentage of 45%. In cycle II, there was an increase of 7 students who had reached KKTP with a percentage of 64% and 4 students had not reached KKTP with a percentage of 36%. In cycle III, it has increased as many as 8 students have reached KKTP with a percentage of 73% and 3 students have not reached KKTP with a percentage of 27%. Furthermore, in cycle IV there was also an increase as many as 11 students had reached KKTP with a percentage of 100%.